EFFECTIVENESS OF COMMUNITY-BASED HEALTH EDUCATION ON PREPAREDNESS FOR FLOOD-RELATED COMMUNICABLE DISEASES IN KELANTAN - Wan Mohammad, Wan Mohd Zahiruddin; Wan Mansor, Wan Nor Arifin; A Hamid, Noor Aman; Sukeri, Surianti; Hasan, Habsah; Yeong Yeh, Lee; Muhd Besari, Alwi; Draman, Nani; Zakaria , Rosnani; Zeehaida Mohamed (Malaysian Journal of Public Health Medicine, 2020)
The flood disaster in Kelantan in 2014 had resulted in substantial health implications including increased cases of communicable diseases. There was a lack of community preparedness including customized health educations in the prevention and control of flood-related communicable diseases in the affected areas. The research was aimed to evaluate the effectiveness of community-based health education modules on flood-related communicable diseases among communities in Kelantan. Health education modules focusing on major food-related diseases were developed. A non-randomized community-controlled trial using the modules were conducted. Outcomes were assessed on knowledge, attitude and preventive practice scores to flood-related communicable diseases using a pre-validated questionnaire. Independent t test was used to compare mean scores between the intervention community (Tumpat) and the control community (Bachok) at 1-month post intervention. One-way independent ANOVA test was done to compare score differences at baseline (pre), post 1-month and post 2-month from repeated surveys among random samples within the intervention community. There were significant improvements in all knowledge components from 9.4% to 52.6% with 10% increment in attitude scores toward preventing behaviours on flood-related communicable diseases. When compared against the control community at one-month post-intervention, there were significantly higher knowledge on types of diseases, symptoms and risk factors as well as practice scores of drinking safe water and protective habits. This research demonstrated that community-based health education is effective in improving relevant knowledge, attitude and preventive practices among affected communities as part of their preparedness toward communicable diseases related to flood.